Optimalisasi Pembelajaran Sejarah Kebudayaan Islam: Mengungkap Esensi Kurikulum Merdeka - Muhammad, Imran (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
ABSTRACTOptimization of learning the history of Islamic culture involves the application of the philosophy of the Merdeka Curriculum as an innovative approach in the world of education. This philosophy offers freedom and creativity for educators in designing learning, especially in the context of teaching the history of Islamic culture. However, challenges arise in implementing these freedoms without creating inequalities or inconsistencies in the curriculum. Adequate training and support for educators is key to ensuring the effectiveness of the implementation of the Merdeka Curriculum. Optimization of learning should also take into account the differences in availability of resources between educational institutions. Efforts need to be made to address this gap and ensure that the implementation of the Merdeka Curriculum can be equitable and inclusive. Nevertheless, the Merdeka Curriculum can be an effective instrument to create a dynamic, relevant, and stimulating historical learning of Islamic culture and deep understanding and appreciation of Islamic values in student life. With a thoughtful approach, the implementation of the Merdeka Curriculum can make a positive contribution in the formation of student character and a broader understanding of Islamic history and culture. ABSTRAKOptimalisasi pembelajaran sejarah kebudayaan Islam melibatkan penerapan filosofi Kurikulum Merdeka sebagai pendekatan inovatif dalam dunia pendidikan. Filosofi ini menawarkan kebebasan dan kreativitas bagi pendidik dalam merancang pembelajaran, khususnya dalam konteks pengajaran sejarah kebudayaan Islam. Namun, tantangan muncul dalam mengimplementasikan kebebasan ini tanpa menimbulkan ketidaksetaraan atau ketidakkonsistenan dalam kurikulum. Pelatihan dan dukungan yang memadai bagi pendidik menjadi kunci untuk memastikan efektivitas penerapan Kurikulum Merdeka. Optimalisasi pembelajaran juga harus mempertimbangkan perbedaan ketersediaan sumber daya antar lembaga pendidikan. Upaya perlu dilakukan untuk mengatasi kesenjangan ini dan memastikan bahwa implementasi Kurikulum Merdeka dapat merata dan inklusif. Meskipun demikian, Kurikulum Merdeka dapat menjadi instrumen yang efektif untuk menciptakan pembelajaran sejarah kebudayaan Islam yang dinamis, relevan, dan merangsang pemahaman mendalam serta apresiasi terhadap nilai-nilai Islam dalam kehidupan siswa. Dengan pendekatan yang bijaksana, implementasi Kurikulum Merdeka dapat memberikan kontribusi positif dalam pembentukan karakter siswa dan pemahaman yang lebih luas terhadap sejarah dan kebudayaan Islam.